PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN KEMANDIRIAN BELAJAR SISWA SMK NEGERI 1 PERCUT SEI TUAN MELALUI PENDEKATAN DIFFERENTIATED INSTRUCTION - Ade Evi Fatimah (Universitas Islam Sumatera Utara, 2016)
AbstractThe research aimed study to determine: 1) the increasing ability of mathematics problem solving and student’s self regulated learning by using Differentiated Instruction is better than students comprehension convensional approach. 2) there was the interaction between learning by students first mathematic ability toward the increasing ability of mathematics problem solving and student’s self regulated learning. This kind of research is the quasi experiment. The populations of this research are all of the students in X grade of Tehnical High School 1 Percut Sei Tuan and the sample choosen is randomly sample which are Tehnical High School 1 Percut Sei Tuan contain with X TKJ1 as experiment class and X TITL1 as control class each consist of 24 students. Instrument used consisted of: (1) test studens first mathematic, (2) test problem solving and (3) self regulated learning scale. The instrument has been declared eligible content validity and reliability coeffesient of 0,809 dan 0,737 respectively for test mathematics problem solving and self regulated learning. Data analysis is done by using ANAVA two ways. The result of this research shown that (1) there increasing ability in mathematics problem solving and student’s self regulated learning by using Differentiated Instruction is better than using students comprehension convensional approach, (2) there were no interaction between learning and student’s ability level to the increasing ability of mathematics problem solving and student’s self regulated learning. The researcher suggests to use the Differentiated Instruction approach as the alternative way for teachers to increase the ability in mathematics problem solving and student’s self regulated learning. Keywords Differentiated Instruction approach, the Ability of mathematics Problem Solving and Student’s self regulated learning